Bibliometric evaluation of 2020–2022 publications on COVID-19-related cardiovascular disease - Chen, Yiru; Cao, Buzi; Zhou, Quan; Liu, Yantong; He, Qingnan; Zhao, Mingyi (Frontiers in Cardiovascular Medicine, 2023)
Objective This study aimed to investigate the international scientific output regarding the relationship between COVID-19 and cardiovascular diseases (CVDs) through a bibliometric analysis and explore research hotspots in this field. Methods We searched the Web of Science Core Collection for publications and used different types of software, such as R, CiteSpace, and VOSviewer, to analyze and visualize the data. Results A total of 10,055 publications were retrieved as of the 13 December 2022, based on the inclusion criteria after screening. The USA and China lead in the quantity and quality of publications in this field. Based on Bradford's law, 63 journals were considered core journals in the field. Co-cited references and keywords analysis indicated that researchers paid particular attention to cardiovascular comorbidities, outcomes, and COVID-19 regenerative medicine. In summary, with increasing COVID-19 research related to CVD, more attention might be drawn to the relationship between these two diseases. Conclusion The hotspots in this field may continue to revolve around cardiovascular comorbidities, outcomes, and COVID-19 regenerative medicine. Owing to the different situations faced by different groups with COVID-19, further exploration of the related factors specific to each of these groups, e.g., history or no history of heart failure, is needed, with a view to providing a reference for intervention measures in COVID-19 research.